Kolaborasi Whatsapp Group, Zoom Cloud Meeting, Dan Google Drive Sebagai Formula Dalam Pelaksanaan Kegiatan Perkuliahan Online Di Masa Pandemi Covid-19 - Kurniawansyah, Arius Satoni; siswanto, siswanto (Jurnal Media Infotama, 2020)
The world of education is facing big challenges with the Covid-19 pandemic. All lecture activities that are usually face-to-face are now prohibited and activities must be carried out online. Many applications are offered for carrying out online lectures, such as Zoom, Google Meeting, Whatsapp Group, and Google Drive and others. Lecturers and students must be capable and literate in technology, if one cannot utilize technology, it will be difficult to carry out online lecture activities. One of the impacts of the COVID-19 pandemic is the change in the school learning system to online. For most learning schools, many things still have to be adjusted, including how to train students to answer questions without them having to cheat by opening the internet. One technology-based learning media that can be used as a support for existing media is in the form of e-learning (electronic learning). E-learning is an internet application that can connect students and educators in an online learning space. E-learning is designed to overcome limitations between educators and students, especially in terms of time, space, conditions and circumstances. In summary, e-learning can create a digital learning space, where students can access material from various sources without being limited by space and time. During the Covid-19 pandemic, it was very effective to carry out online lectures using the Zoom application, Whatsapp Group and Google Drive.